Development of Cheerful Ludo Math Integrated With Tgt Model for Solving Fifth Grade Mathematical Story Problems - Ratnasari, Esti Ayu; Nugraheni, Nursiwi (Jurnal Pendidikan MIPA, 2025)
Abstract: The purpose of this research is to develop a ludo media called cheerful math ludo (Domaria), which is integrated with the TGT model to solve fifth-grade math story problems based on the material of the volume of space. The type of research used is R&D with the Borg and Gall model. The stages in this research are analyzing problems, collecting data, making product designs, design validation, design revisions, small group trials, product revisions, and large group trials. Based on validation from media experts of 91.7% (very feasible), material experts of 91.7% (very feasible), and language experts of 81.3% (very achievable), as well as the results of teacher and student responses of 100% (very feasible), it shows that Domaria media is suitable for use. This can be seen from the results of the paired T-test in small groups with a Sig value. (2-tailed) 0.000, which means that the average post-test value has increased when compared to the pre-test value. Then, the N-Gain test in the small group obtained a result of 0.627, which means that it is effective in the medium category. The same thing happened in the paired T-test test in the large group, which showed a sig value. (2-tailed) 0.000, which means that the average post-test value increases from the previous pre-test average. The large group N-Gain test showed a value of 0.699, which was said to be effective in the medium category. Thus, Domaria media integrated with the TGT model is proven to be effective for teaching and learning.     Keywords: learning media, ludo, TGT model, mathematics.